“Do as we say and you'll be successful”: Mundane power in corporate entrepreneurship - Skade, Lorenzo; Wenzel, Matthias; Koch, Jochen (The Journal of product innovation management, 2024)
Corporate entrepreneurship is infused with power. Prior research has begun to shed light on the role of power in innovation contexts. Yet, we know much less about the day‐to‐day enactment of mundane power in corporate entrepreneurship, which, despite its partial subtlety, is no less consequential regarding decisions on pursuing or abandoning innovative ideas. This paper extends the literature on corporate entrepreneurship and power by exploring the discursive practices through which managers and employees of a corporate accelerator disciplined venture founders in the pursuit of innovative ideas. Based on a Foucauldian discourse analysis of ethnographic data, we show how a clash of entrepreneurship discourses invokes the day‐to‐day performance of three discursive practices—observing, exercising, and punishing—through which the accelerator's staff ensured that venture founders would adopt a dominant entrepreneurship discourse, with important implications for decisions on pursuing innovative ideas or not. These findings deepen our understanding of enacting mundane power in corporate entrepreneurship as well as the enablers and outcomes of such power enactment. We also outline the practical implications for emerging corporate innovation settings such as accelerators.